Investigating The Grammatical Interference of Indonesian-Gayonese EFL Learners - Munandar, Imam (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2023)
This study aimed to investigate the causes of Indonesian interference in the writing of English as a Foreign Language (EFL) students and to examine the types of such interference. In order to figure out the issue of Indonesian grammatical interference, a descriptive qualitative approach was adopted by utilizing fourth-semester students of the English Department IAIN Takengon, Aceh, Indonesia, as the target population for the research. Subsequently, the data was derived from both tests and observations. Data analysis indicates that the students still experienced interference from the Indonesian grammar due to it being their first language. In this research, grammatical interference is divided into two categories: the interference of syntax and morphology. Syntactic interference comprises words, prepositions, superfluous words, and word omission. The most prevalent occurrence of syntactic interference is in the area of prepositions. Morphological interference replicated itself in determiner omission, incorrect determiner usage, subject-verb agreement discrepancies, the incorrect verb 'to be,' incorrect usage of verb tenses, and confusion regarding singularity and plurality. Though, the most prevalent type of morphological interference is the omission of a determiner. It was observed that the disparity in the structure of Indonesian and English grammar accounts for the interference. In addition, another cause was that students typically composed it first in Indonesian and translated it into English.